A partnership model in the development and implementation of a collaborative, cardiovascular education program for Aboriginal Health Workers - Davidson, Patricia; DiGiacomo, Michelle; Abbott, P.; Zecchin, R.; Heal, P.; Mieni, L.; Sheerin, N.; Smith, J.; Mark, A.; Bradbery, B.; Davison, J. (Australasian Medical Publishing Company Pty Ltd, 2008)
Background: Aboriginal Health Workers (AHWs) play a vital role in accessing communities and implementing culturally appropriate interventions to address cardiovascular risk factor modification.Aim: To assess the feasibility and acceptability of a collaborative model of cardiovascular education for AHWs conducted within a partnership model.Method: A steering committee was established using a partnership model between key education providers, policy makers, non-government organisations, the local area health service and Aboriginal community controlled organisations. This group negotiated a strategic implementation plan based on increasing collaboration, skill development, cultural competence and increasing access to mentorship and expertise for AHWs. A group of 21 AHWs, within two cohorts, undertook the program between October 2005 and June 2006. A mixed-method evaluation using quantitative and qualitative data collection methods was undertaken prospectively.Findings: Knowledge and confidence scores significantly increased for all participants over the course duration. Student evaluation demonstrated a desire for group based activities and highly valued clinical visits. Feedback on both outcome and process measures will inform course delivery and design.Conclusion: Improvements in cardiovascular knowledge scores and levels of confidence are indicative of the efficacy of the curriculum design and course delivery method. The partnerships forged in this collaborative model have significant and promising implications for improving the cardiovascular health of Aboriginal Australians.